Zooglider‐measured association of zooplankton with the fine‐scale vertical prey field. Issue 10 (13th September 2021) - Whitmore, Benjamin M.; Ohman, Mark D.
Abstract: We use Zooglider, a low‐power optical zooplankton‐sensing glider, to test the covariability of the fine‐scale vertical distributions of six omnivorous zooplankton taxa with three different representations of their potential prey field: small suspended particles (equivalent circular diameter [ECD] between 0.25 and 0.45 mm), marine snow (ECD ≥ 0.45 mm), and chlorophyll a (Chl a ), in the San Diego Trough. All three prey fields tend to be highly correlated from 100 m to the depth of the subsurface Chl a maximum layer (SCML), while correlations between the prey fields are weaker or nonexistent from the SCML to the surface. An index of spatial overlap (Local Index of Collocation) showed stronger overlap of zooplankton with marine snow or small particles than with Chl a in most cases. Moreover, generalized additive models revealed marine snow distributions or small particles as the primary explanatory variable, by percent deviance explained, for all zooplankton taxa tested. Chl a distributions were a secondary explanatory variable for four of the six taxa tested (small copepods, appendicularia‐ Fritillaria, and both night and day large copepods), and an insignificant explanatory variable for the remaining two (appendicularia‐others and large protists). The distributions of suspended particles, during our year‐round study in the San Diego Trough, were more informative for explaining distributions of omnivorous zooplankton than Chl a alone.